By canoe and dog-train among the Cree and Salteaux Indians [electronic resource] - Young, Egerton Ryerson, 1840-1909.; Pearse, Mark Guy, 1842-1930. (New York; Cincinnati : Abingdon Press, 1890)
'"Out of the darkness of night ."' Electronic reproduction. Mode of access: Internet. 44